Detection of ubiquitinated huntingtin species in intracellular aggregates - Juenemann, Katrin; Wiemhoefer, Anne; Reits, Eric A. (Frontiers in Molecular Neuroscience, 2015)
Protein conformation diseases, including polyglutamine diseases, result from the accumulation and aggregation of misfolded proteins. Huntington’s disease is one of nine diseases caused by an expanded polyglutamine repeat within the affected protein and is hallmarked by intracellular inclusion bodies composed of aggregated N-terminal huntingtin fragments and other sequestered proteins. Fluorescence microscopy and filter trap assay are conventional methods to study protein aggregates, but cannot be used to analyze the presence and levels of post-translational modifications of aggregated huntingtin such as ubiquitination. Ubiquitination of proteins can be a signal for degradation and intracellular localization, but also affects protein activity and protein-protein interactions. The function of ubiquitination relies on its mono- and polymeric isoforms attached to protein substrates. Studying the ubiquitination pattern of aggregated huntingtin fragments offers an important possibility to understand huntingtin degradation and aggregation processes within the cell. For the identification of aggregated huntingtin and its ubiquitinated species, solubilization of the cellular aggregates is mandatory. Here we describe methods to identify post-translational modifications such as ubiquitination of aggregated mutant huntingtin. This approach is specifically described for use with mammalian cell culture and is suitable to study other disease-related proteins prone to aggregate.